A Transient Grating Method to Measure the Dispersion of Elastic Waves in Nanostructures. (March 2020) - Charron, E.; Lu, L.; Bonello, B.; Boyko, O.; Glushkov, E.; Glushkova, N.; Tchernycheva, M.; Gogneau, N.
Abstract: We describe the so-called " Transient Grating Method " which is a non-invasive experimental technique well suited to measure the dispersion properties of ordered or disordered nanostructures and thin films, at frequencies up to a few GHz. This pump-and-probe technique involves the interference pattern produced by two in-coming IR optical pulses to set a standing elastic wave on the surface of the sample through photoelastic processes. The wave vector of this elastic wave can be easily tuned by adjusting the angle between the two incident beams. Two continuous visible laser beams in a heterodyne detection scheme are used to detect the vibrations on the surface and in turn the dispersion of the related elastic modes. The achievements of the technique are illustrated by the measurement of the dispersion of surface acoustic waves in piezogenerators consisting of GaN nanowires embedded into a dielectric matrix (HSQ). We then report on the analysis of the experimental data that allowed extracting the elastic parameters of this composite medium.